Safar-i Miṣr va Jalāl Āl Aḥmad va Falasṭīn - Baraheni, Reza, 1935- (Nashr-i Avval, 1984)
Travel impressions of Egypt, 1971; includes an analysis of the views of Jalāl Āl Aḥmad, Persian litterateur, on the Palestine issue.